Terrestrial Lords? An onomastic view on Zemopacios in Lasitius - Sommer, Florian (Vilnius University Open Series, 2022)
The present paper presents evidence for treating the expression Zemopacios in Lasitius’ De diis samagitarum […] as referring to the totality of divinities enumerated in the text’s catalogue of gods. Such an extension of reference was made possible by secondarily motivating the name as if connected with žemas “low”. Consequently, Zemopacios adopted traits of an appellativum.